Asset Allocation and Monetary Policy: Evidence from the Eurozone - Harald Hau; Sandy Lai (Center for Economic Studies and ifo Institute (CESifo), 2014)
The eurozone has a single short-term nominal interest rate, but monetary policy conditions measured by real short-term interest rates varied substantially across countries in the period 2003-2010. We use this cross-country variation in the (local) tightness of monetary policy to examine its influence on equity and money market flows. In line with a powerful risk-shifting channel, we find that fund investors in countries with decreased real interest rates shift their portfolio investment out of the money market and into the riskier equity market - causing significant equity price inflation in countries where investment home bias is the strongest.
Keywords: G11; G14; G23; 330; monetary policy; asset price inflation; risk seeking; Taylor rule residuals